2013
DOI: 10.1002/jcb.24551
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mechanisms of glutathione‐dependent chemistry in biology and disease

Abstract: Glutathione has traditionally been considered as an antioxidant that protects cells against oxidative stress. Hence, the loss of reduced glutathione and formation of glutathione disulfide is considered a classical parameter of oxidative stress that is increased in diseases. Recent studies have emerged that demonstrate that glutathione plays a more direct role in biological and pathophysiological processes through covalent modification to reactive cysteines within proteins, a process known as S-glutathionylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 50 publications
0
19
0
2
Order By: Relevance
“…While some proteins form intermolecular disulfide bonds with other thiol oxidoreductases (e.g., thioredoxins), many proteins also undergo reversible redox chemistry with small molecule thiols like GSH [54]. Therefore, we explored whether DVSF could be used to detect GSH conjugates of several proteins that are prone to S -glutathionylation during oxidative stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While some proteins form intermolecular disulfide bonds with other thiol oxidoreductases (e.g., thioredoxins), many proteins also undergo reversible redox chemistry with small molecule thiols like GSH [54]. Therefore, we explored whether DVSF could be used to detect GSH conjugates of several proteins that are prone to S -glutathionylation during oxidative stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Methionine is also involved in glutathione formation, which serves as an antioxidant [ 111 ]. Lowered glutathione level is a biomarker of oxidative stress [ 112 ], and may contribute to chronic inflammation and cancer development [ 113 ]. These observations suggest that lowered methionine levels may also play a role in the precipitation of cancer cell proliferation, through the reduction in antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested that Cys 249 is a functionally important S ‐glutathiolation site in C1‐M‐C2. S ‐glutathiolation has been reported to alter protein function by modifying protein‐protein interactions or inducing changes in the structural conformation of a modified protein (53). S ‐glutathiolation at Cys 249 occurs near the phosphorylation sites and is therefore likely to have an impact on protein kinase interaction with cMyBP‐C and subsequent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%